AGRO-MORPHOLOGICAL STUDIES ON EFFECT OF ORGANIC MANURES AND BIOINOCULANTS ON VEGETATIVE AND YIELD ATTRIBUTES OF GYMNEMA (GYMNEMA SYLVESTRE R.BR) - S. MANIGANDAN,; K. MANIVANNAN, (The Bioscan, 2015)
A field experiment was conducted to study the influence of organic manures and bio-inoculants on vegetative and yield attributes of gymnema (Gymnema sylvestre R.Br). The experiment was laid out in Randomized Block Design with nine treatments. The study showed significant differences among the treatments. Among treatment combination Vermicompost (1 kg) + Consortium Bio fertilizers @10 g plant-1 + Humic acid 0.2 % foliar spray, recorded maximum plant height (78.25 and 203.35 cm), No. of laterals/ plant (46.52) at all stages of plant growth. With respect to yield, application of Vermicompost(1 kg) + Consortium Bio fertilizers+ Humic acid @ 0.2 % foliar spray was found to be bestfor fresh leaf yield plant-1 (926.23 g)and dry leaf yield plant-1 (601.58 g)and minimum was noticed in control. Thus, it can be concluded from the findings that application Vermicompost(1 kg) + Consortium Bio fertilizers+ Humic acid @ 0.2 % foliar spray can be recommended for commercial cultivation of Gymnema.